2021
DOI: 10.1021/acs.jpcc.1c02171
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of Extraframework Al3+ Cations and Brønsted Acid Sites on Hierarchical ZSM-5 Zeolites for Butanol-to-Olefin Conversion

Abstract: ZSM-5 zeolite catalyzed dehydration of biobutanol has been widely used for the sustainable production of butene. Brønsted acid sites (BASs) in zeolites usually act as catalytically active sites. Lewis acid sites (LASs) are also active for alcohol dehydration. Therefore, extraframework aluminum species have been introduced to zeolites as LASs. Tricoordinated Al species are the strongest LASs, which can enhance the acidity of adjacent surface BASs. Here, we combined solid-state nuclear magnetic resonance (NMR) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…The ZSM-5 was prepared in our lab according to the published method. 37 After 6 h of reaction at 90 °C, 35.5% DHA conversion was achieved with a broad product distribution: 59.0%, 65.9%, and 6.9% as PADA, EL, and PAEA, respectively. The broad product distribution dominated by PADA can be rationalized by the presence of strong Brønsted acid sites in the ZSM-5 catalyst., 38,39 illustrating the advantage of moderate Brønsted acidity with Lewis acid sites in HfNDI in catalyzing a selective DHA-to-EL transformation reaction.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The ZSM-5 was prepared in our lab according to the published method. 37 After 6 h of reaction at 90 °C, 35.5% DHA conversion was achieved with a broad product distribution: 59.0%, 65.9%, and 6.9% as PADA, EL, and PAEA, respectively. The broad product distribution dominated by PADA can be rationalized by the presence of strong Brønsted acid sites in the ZSM-5 catalyst., 38,39 illustrating the advantage of moderate Brønsted acidity with Lewis acid sites in HfNDI in catalyzing a selective DHA-to-EL transformation reaction.…”
Section: Resultsmentioning
confidence: 94%
“…Lastly, an aluminum-doped zeolite, ZSM-5, was used as a heterogeneous catalyst for DHA conversion. The ZSM-5 was prepared in our lab according to the published method . After 6 h of reaction at 90 °C, 35.5% DHA conversion was achieved with a broad product distribution: 59.0%, 65.9%, and 6.9% as PADA, EL, and PAEA, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The Louis group confirmed that extra-framework aluminum species worked as Lewis acid sites to selectively activate C–H bonds of isobutane at low temperature . The synergy between tricoordinated Al species and bridging OH groups to form ultrastrong acid sites for biobutanol conversion was investigated by Huang and coworkers by 1D and 2D multinuclear NMR …”
mentioning
confidence: 93%
“…23 The nature and spectroscopic expression of external surface sites of zeolites such as silanol−Al sites by the combination of MAS NMR and Fourier-transform infrared spectroscopy (FT-IR) with DFT calculations was investigated by the Chizallet group. 24 Koller and coworkers observed additional 1 H− 27 Al dipolar interactions in an extra-large pore zeolite with high aluminum ordering using 1 H{ 27 Al} rotational echo adiabatic passage double-resonance. 25 The Louis group confirmed that extra-framework aluminum species worked as Lewis acid sites to selectively activate C−H bonds of isobutane at low temperature.…”
mentioning
confidence: 99%
See 1 more Smart Citation